Pengaruh Pengalaman Auditor, Locus of Control dan Pengetahuan Mendeteksi Kekeliruan terhadap Audit Judgment di Kantor BPKP Perwakilan Sumatera Utara - Antonius KAP Simbolon; Ruth Anggie Panjaitan; Jitro Sebayang; Chintya Tarihoran; Monica Lb Tobing (Politeknik Ganesha Medan, 2019)
The auditor is a profession whose job is to audit financial statements. This research was aimed to obtain empirical evidents on effects of auditor’s experience, locus of control and knowledge to detect mistakes positive effect on audit judgment. This research was conducted at BPKP Sumatera Utara province with the primary data collection method is using questionnaire data. The samples used are 95 people is calculated using the formula Slovin. Data have valid and reliable, meet the classic assumption test. The analysis technique used is Multiple Linear Regression Analysis with software SPSS. The results of the research showed that auditor’s experience, locus of control and knowledge to detect mistakes have a significant positive effect on audit simultan and partial judgment